2016
DOI: 10.1002/app.43784
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of macroporous amphoteric cryogels based on N,N‐dimethylaminoethyl methacrylate and methacrylic acid with dyes, surfactant, and protein

Abstract: Macroporous amphoteric cryogels based on N,N-dimethylaminoethylmethacrylate and methacrylic acid p(DMAEM-co-MAA) crosslinked by N,N 0 -methylenebisacrylamide (MBAA) were synthesized by radical copolymerization of monomer mixtures in cryoconditions. The structure and morphology of cryogels were evaluated by FTIR and SEM. Cryogels exhibited interconnected porous structure with pore size ranging from 40 to 80 mm, which depended on their crosslinking degree. The value of the isoelectric point (IEP) of equimolar am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…Due to their interconnected, macroporous 3D structure, cryogels have been widely used in bioseparation‐related applications [1–10], tissue engineering [10–14], and other relevant bioengineering and sensor applications [15–17]. In particular, monolithic cryogels have been used as a new generation of chromatographic matrices for the separation of cells (mammalian, bacterial, and yeast), proteins, viruses, and plasmids [18–22].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their interconnected, macroporous 3D structure, cryogels have been widely used in bioseparation‐related applications [1–10], tissue engineering [10–14], and other relevant bioengineering and sensor applications [15–17]. In particular, monolithic cryogels have been used as a new generation of chromatographic matrices for the separation of cells (mammalian, bacterial, and yeast), proteins, viruses, and plasmids [18–22].…”
Section: Introductionmentioning
confidence: 99%
“…The idea of the use of macroporous and supermacroporous cryogels as flow-through catalytic reactors was for the first time suggested in [12] and experimentally realized in [7,[26][27][28][29][30] for hydrogenation of nitroaromatic compounds ( Figure 7). Later on Sahiner et al [31,32] using the same principles and glass column reactor repeated reduction of 4-nitrophenol (4-NP) to corresponding 4-aminophenol (4-AP) with the help of superporous cryogels containing various metal nanoparticles and were able to lower the activation energy (E a ) of catalytic reduction of 4-NP considerably in comparison with similar studies reported in the literature.…”
Section: Flow-through Catalytic Reactors Based On Macroporous Cryogelmentioning
confidence: 99%
“…Equimolar polyampholyte cryogel P(DMAEM-co-MAA) synthesized from acidic and basic monomers, such as N,N-dimethylaminoethylmethacrylate (DMAEM) and methacrylic acid (MAA) effectively reduces rhodium, palladium, gold and silver ions under heating conditions and forms fine well-dispersed metal nanoparticles without the use of any other reducing agents [30]. Moreover micron-sized cryogel matrix provides fast swelling during 0.5-2 min and high water flux [26].…”
Section: Flow-through Catalytic Reactors Based On Macroporous Cryogelmentioning
confidence: 99%
“…The feasibility of the “isoelectric effect” was tested for crosslinked amphoteric macroporous cryogels consisting of N , N -dimethylaminoethylmethacrylate and methacrylic acid (DMAEM- co -MAA) with respect to surfactant—sodium dodecylbenzene sulfonate (SDBS), dyes methylene blue (MB) and methyl orange (MO), and protein lysozyme [155]. It was found that the release efficiency of dye, surfactant and protein at the IEP from amphoteric cryogel (pH IEP = 7.1) can reach up to 98%.…”
Section: Realization Of the ‘Isoelectric Effect’ At The Isoelectrimentioning
confidence: 99%